Geomagnetic Activity Index Hpo. Issue 10 (13th May 2022) - Yamazaki, Y.; Matzka, J.; Stolle, C.; Kervalishvili, G.; Rauberg, J.; Bronkalla, O.; Morschhauser, A.; Bruinsma, S.; Shprits, Y. Y.; Jackson, D. R.
Abstract: The geomagnetic activity index Kp is widely used but is restricted by low time resolution (3‐hourly) and an upper limit. To address this, new geomagnetic activity indices, Hpo, are introduced. Similar to Kp, Hpo expresses the level of planetary geomagnetic activity in units of thirds (0o, 0+, 1−, 1o, 1+, 2−, …) based on the magnitude of geomagnetic disturbances observed at subauroral observatories. Hpo has a higher time resolution than Kp . 30‐min (Hp30) and 60‐min (Hp60) indices are produced. The frequency distribution of Hpo is designed to be similar to that of Kp so that Hpo may be used as a higher time‐resolution alternative to Kp . Unlike Kp, which is capped at 9o, Hpo is an open‐ended index and thus can characterize severe geomagnetic storms more accurately. Hp30, Hp60 and corresponding linearly scaled ap30 and ap60 are available, in near real time, at the GFZ website (https://www.gfz-potsdam.de/en/hpo-index ). Plain Language Summary: The geomagnetic activity index Kp is a measure of planetary geomagnetic activity, expressed in units of thirds (0o, 0+, 1−, 1o, 1+, 2−, …9o). Kp is widely used in the space physics community, as it is known to be a good proxy of the solar‐wind energy input into the magnetosphere‐ionosphere‐thermosphere system. Kp has two important limitations. One is the temporal resolution. Kp is a three‐hourly index, so that temporal features within 3 hr are not resolved. The other is the upper limit of the index. Kp does not exceed a maximum value of 9o, so that under extremely disturbed conditions, geomagnetic activity is not accurately represented. We introduce a group of new geomagnetic activity indices Hpo that overcomes these limitations. Hpo is designed to represent planetary geomagnetic activity in a similar way as Kp but with higher temporal resolution and without the upper limit at 9o. This paper describes the production of 30‐min (Hp30) and 60‐min (Hp60) indices, and demonstrates their properties in comparison with Kp . Hpo indices since 1995, including near‐real‐time values, are distributed through the GFZ website (https://www.gfz-potsdam.de/en/hpo-index ). Key Points: New Kp ‐like planetary geomagnetic activity indices, Hpo, are presented Hourly (Hp60) and half‐hourly (Hp30) indices are available from GFZ website Hpo indices are open‐ended without the upper limit at 9o